Factors associated with parent views about participation in infant MRI research provide guidance for the design of the Healthy Brain and Child Development (HBCD) study. (August 2021) - Kohlasch, Kaelyn L.; Cioffredi, Leigh-Anne; Lenninger, Carly; Stewart, Ellen; Vatalaro, Tessa; Garavan, Hugh; Graham, Alice; Heil, Sarah H.; Krans, Elizabeth E.; Robakis, Thalia; Rommel, Anna; Sullivan, Elinor L.; et al.
Abstract: Purpose: The National Institutes of Health announced the Healthy Brain and Child Development (HBCD) study to further understanding of infant brain development. This study examined perceptions and knowledge about research among the demographic groups to be studied in HBCD. Method: 1164 participants (n = 548 pregnant people and 616 mothers of infants < 12 months) completed anonymous, on-line surveys. Domains included research literacy, MRI knowledge, and attitudes about research incentives and biospecimen collection. Logistic regression was used to examine factors related to outcome variables. Results: Knowledge of MRI safety was low and research literacy was high across participants. Likelihood of participation given various incentives differed between participants. Those with lower education were less likely to rate any items as increasing likelihood of participation. Substance use during pregnancy improved the model fit only for items about alternate visit structures (home and telephone visits) and confidentiality. Conclusion: Overall results support the feasibility of infant imaging studies, such as HBCD with respondents having high research literacy and interest in learning about their baby's development. Educating potential participants about MRI safety and providing flexible incentives for participation will improve the success of infant MRI studies.